Mediation Effect of Work Motivation on the Relationship between Soft Skills and Hard Skills, and Impact on Employee Performance in Skincare Clinical - Ermina Rusilawati (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
Employee motivation serves as an indicator of the level of enthusiasm, commitment, and originality that employees direct towards their job responsibilities. This study aims to investigate the effects of both interpersonal skills and technical skills on employee performance, while also examining whether work motivation plays a role in the Clinical Skincare context in Pekanbaru. The study encompasses all personnel associated with the Skincare Clinic in 2019. Using a comprehensive approach, a total of 32 individuals from the clinic were chosen as the study's participants. Data essential for the research was gathered through surveys administered to the clinic's staff. To assess the hypotheses, Structural Equation Modeling (SEM) analysis was conducted utilizing the Partial Least Squares (PLS) method. The results demonstrate that: (1) Interpersonal skills have a positive influence on work motivation. (2) Technical skills have a positive impact on work motivation. (3) Interpersonal skills positively affect employee performance. (4) Technical skills have a favorable effect on performance. (5) Work motivation significantly contributes to performance. (6) Motivation serves as a partial mediator between interpersonal skills and performance. (7) Work motivation does not act as a mediator in the relationship between technical skills and performance. As a suggestion, future researchers are encouraged to explore alternate mediating variables that could impact the association between technical skills and employee performance.